OPTIMIZATION OF A GOOD GOVERNANCE SYSTEM THROUGH SYNERGY AND COLLABORATION BETWEEN LEADERSHIP AND BUREAUCRACY IN INDONESIA - Agung, Magda Faradiba Mauludia; Rani, Berliana Mustika; Millensyah, Erwing Wahyu; Wijayanto, Hendra; Sari, Sarah Meirina; Perdana, Rizky Nurhidayat (Departemen Administrasi Publik, Universitas Diponegoro, 2025)
Good governance is a crucial foundation for sustainable development in Indonesia. Its implementation, however, faces various challenges, including weak coordination between leadership and bureaucracy. This article aims to examine the role of synergy and collaboration between visionary leadership and professional bureaucracy in achieving effective, transparent, and accountable governance. This research employs a qualitative approach based on literature studies and policy analysis, focusing on case studies of bureaucratic reform in several regions of Indonesia. The findings indicate that a harmonious relationship between leadership and bureaucracy can enhance public service effectiveness, accelerate policy implementation, and minimize corruption. Responsive leadership serves as the primary driver of change, while professional bureaucracy acts as an efficient policy executor. The challenges include resistance to change, political influence, and overlapping bureaucratic authorities. Addressing these challenges requires strategic measures such as strengthening leadership training, performance-based bureaucratic reforms, and the adoption of digital technology to enhance transparency and efficiency. Strong synergy and good governance can be optimized to meet societal needs and global challenges.